P38 MAPK/miR‐1 are involved in the protective effect of EGCG in high glucose‐induced Cx43 downregulation in neonatal rat cardiomyocytes. (28th June 2016) - Yu, Lu; Yu, Hongmei; Li, Xiaoting; Jin, Chongying; Zhao, Yanbo; Xu, Shengjie; Sheng, Xia
Abstract: The remodeling of cardiac gap junctions contributes to various arrhythmias in a diabetic heart. We previously reported that Epigallocatechin‐3‐gallate (EGCG) attenuated connexin43 (Cx43) protein downregulation induced by high glucose (HG) in neonatal rat cardiomyocytes, but Cx43 mRNA expression was not affected. It indicated the possible mechanisms of post‐transcriptional regulation, which still remains unclear. As microRNAs (miRNAs) regulate gene expression widely at post‐transcriptional level, we measured miR‐1/206 in cardiomyocytes treated with HG and EGCG by quantitative RT‐PCR and investigated their relationship with signal transduction pathways. The results showed that HG induced miR‐1/206 elevation by PKC MAPK pathway. Moreover, we tested the negative regulation effect of miR‐1/206 on Cx43 protein by miRNAs transfection. EGCG, however, nearly abolished the HG‐induced miR‐1 augmentation via P38 MAPK pathway. Therefore, our study suggested that PKC‐activated miR‐1/206 expression might contribute to Cx43 downregulation in HG‐treated cardiomyocytes, and EGCG conferred protective effect by inhibiting miR‐1 elevation via P38 MAPK pathway.